2018
DOI: 10.1080/10410236.2018.1461585
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Theory of Resilience and Relational Load (TRRL) in Families with Type I Diabetes

Abstract: The theory of resilience and relational load was tested with 60 couples and their adolescent children (ages 11-18) with type I diabetes (T1D). The couples participated in a stress-inducing conversation task in their home, followed by a random assignment to a two-week intervention designed to increase their relationship maintenance. Before the intervention, stronger communal orientation predicted greater maintenance for husbands and wives, but maintenance only reduced T1D stress for wives. The wives' and adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 51 publications
5
37
0
Order By: Relevance
“…Perhaps for these reasons, for mothers with more avoidant partners, motherhood may be perceived as particularly stressful because their partners engage less in common DC. Although previous studies conducted with families with type I diabetes showed that feeling communally oriented toward one's partner reduced fathers', but not mothers', perceived parenting stress (Afifi et al, ), for women transitioning to first‐ or second‐time parenthood, a communal approach to stressors (at least at the behavioral level) seems to play an important role. This explanation may also account for why these mothers also feel less confident in their role.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Perhaps for these reasons, for mothers with more avoidant partners, motherhood may be perceived as particularly stressful because their partners engage less in common DC. Although previous studies conducted with families with type I diabetes showed that feeling communally oriented toward one's partner reduced fathers', but not mothers', perceived parenting stress (Afifi et al, ), for women transitioning to first‐ or second‐time parenthood, a communal approach to stressors (at least at the behavioral level) seems to play an important role. This explanation may also account for why these mothers also feel less confident in their role.…”
Section: Discussionmentioning
confidence: 83%
“…Our findings suggest that, when mothers are willing to engage in collaborative strategies when dealing with daily demands, fathers become more involved in the family's everyday concerns and are perhaps better equipped to manage their insecurities. Fathers might feel that they are “part of a team,” which has been shown to be of particular relevance for fathers of young children (Afifi et al, ). Consequently, this should foster their own sense of competence in their parenting skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the emotional capital hypothesis contribute to a growing body of literature showing that greater maintenance is linked to less stress in a variety of contexts, including chronic illness (Afifi et al, 2018) and fast-paced families (Afifi, Harrison, Zamanzadeh, & Acevedo Callejas, 2019). It also compliments research that has found that positive relational maintenance behaviors are associated with lower levels of conflict (Driver & Gottman, 2004; Goodboy, Dainton, Borzea, & Goldman, 2017; Merolla, 2017).…”
Section: Discussionmentioning
confidence: 88%
“…The combination of communal orientation and relationship maintenance impacts how couples communicate when they are stressed, as well as how they appraise stressors (Afifi et al, 2016, 2018). When couples do not feel emotionally connected or take the time to invest in their relationships, their primary motivation is to protect themselves when they are stressed rather than their partner or their relationship; they see their partner as a “threat” rather than a source of “security” during stressful and conflict-inducing situations.…”
Section: The Trrlmentioning
confidence: 99%